PENGEMBANGAN PEMBELAJARAN ONLINE PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Muhammad Yusuf; Faridah; Nanda Saputra (Bajang Institute, 2022)
This paper aims to identify and analyze the development of blended learning. This research is a literature review (Library Research). As for the results of the search from the author, it shows that blended learning is a long distance learning system which requires tools to transfer knowledge to students, namely via the internet or a network. Moreover, in blended learning, developments are needed, including doing Web-based online learning, Moodle-based learning, and Poodle-based learning ( Portable Moodle). A good model for developing Islamic Religious Education learning to use is the moodle and quipper school in which there are many applications that make it easier to learn Islamic Religious Education. The implication of the development of this learning is to become the right solution that can be applied in online learning, particularly during this current pandemic situation.